Shopping centers, sociabilidade e conflitos socioespaciais urbanos - João Victor Sanches Patrício; William Ribeiro da Silva (Confins)
Shopping malls are important equipment that influence the redefinition of centralities and the spatial logic of sociability and contemporary urban conflicts. In this sense, this article aims to discuss and analyze socio-spatial conflicts produced by the implementation of a shopping mall in the Juiz de Fora (MG), located near a neighborhood formed by the quilombola community, where a social movement was organized that challenged actions of the Independência Shopping. We opted for a methodology with interviews and research from secondary sources, with emphasis on social networks (Facebook) and corporate websites. It was concluded that the polycentric city increases the complexity in the reproduction of spaces and enhances the occurrence of conflicts by spatially expanding the interest of capitalist agents in the urban production, with the shopping mall as one of the central elements.